Pengaruh Do’a terhadap Tekanan Darah pada Pasien Gagal Ginjal Kronis (GGK) Pre-Hemodialysis - Hilda Nur Afriani; Rohman Azzam; Busrja M.Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of interventional prayer on pre-hemodialysis blood pressure in patients with chronic renal failure in the hemodialysis room at the Islamic Hospital in Jakarta. The research method uses quasi experiment method. The results of the study found a decrease in blood pressure in the intervention group after the intervention both in systolic and diastolic blood pressure. Paired t-test results before and after the given intervention in the intervention and control groups produced a sig value <0.05 in systolic and diastolic blood pressure, meaning that there were differences before and after the intervention was given. The unpaired t-test results between the intervention and control groups of systolic blood pressure produce a sig value> 0.05, meaning that there is no difference between the intervention and control groups while the diastolic blood pressure produces a sig value <0.05, meaning that there are differences between the intervention and control groups. Conclusion, the administration of prayer interventions in pre-hemodialysis is proven to reduce blood pressure. Keywords: Prayer, Chronic Kidney Failure, Blood Pressure